Effect of inquiry science learning on students’ metacognitive skill - Lelasari, Tarsiana; Yohanita, Aksamina Maria; Damopolii, Insar (Univeritas Papua, 2021)
This study aims to determine the effect of the inquiry learning model on the metacognitive skills of class XI science students at SMA Negeri 1 Manokwari. This study used a quasi-experimental approach with a non-equivalent control group. This study took samples of two groups, namely the XI MIA 4 group as the experimental group, and the XI MIA 7 group as the control group. Purposive sampling is used in the sample method. The instrument used is a test consisting of 12 questions in the form of a description. The findings show that the average final metacognitive ability of the experimental group is 61.22, while the average of the control group is 46.69. The data analyst used the Mann-Whitney non-parametric test to determine whether there was a difference in metacognitive ability between students using the inquiry model and students using the conventional model. P= 0.012 < 0.05 indicates that there are differences in metacognitive skills between students who use the inquiry model and students who use the conventional model.